O caminho das águas: impactos ambientais da drenagem de águas pluviais na bacia do Córrego Liso na cidade de Uberlândia-MG - Péres, Rosa Helena Borges (2005)
The observation of the effects caused by the superficial outlet of rain waters in the area of Córrego Liso Bay, in the city of Uberlândia-MG, has motivated the accomplishment of this work. Those effects, very often represented by intense erosive processes, being more visible in the Permanent Preserving areas, could have a relationship with all the system of drainage nets of rain waters and not only with the superficial outlet. With the aim in finding the possible interferences and the generator agents of the environmental impacts on the Córrego Liso Bay, it was done over different ways, such as: analysis of projects, pictures and direct observation on the studied area, questionaires applied to experienced professionals in Urban Drainage and to employees from the local Public Power. Once identified the problems, it was then found a lot of interferences from the urbanization into the drainage system, finally defining the shocking agents: Public Power, population, engineering professionals, rain waters drainage system, plots enterprisings. It can be added to the impacts caused by these agents, the fragility of the natural resources of the area, like the soils that are very susceptible to erosions or the lack of vegetation. At the end of the work it was presented a series of suggestions in an attempt to control and recover those effects, including facilities for the Public Power action. It s believed that it is imperative to form a group action for the environmental education for those agents in order to generate a changing in attitudes that can move them towards the preservation and prevention, without letting the Public Power work by itself.